(untitled) (Journal Of Educational and Psychological Researches, 2016)
The current study aims at identifying of the differences of life quality level for the academic instructors at Omar Al-Mukhtar University / Libya according to the city variable that the instructor belong to ( Libya, Iraq, Egypt ), and also according to gender Variable (Male - Female),To achieve the aims of study ,the researcher chose a sample consists of (210) instructors ( 170 males and 40 females) from four colleges at Omar Al- Mukhtar University/ Darna . The researcher built the scale of life quality which consists of (42) items in last version . The researcher has conducted the validity and reliability of the scale. and by using Analysis of Variance via (SPSS program). The research reaches the following results : 1-The life quality of the instructors was low with Statistically significant . 2-There were differences in life quality according gender and the favorite of females with Statistically significant (0.01). 3-There were differences in life quality between samples (Egyptian-Libyan , Egyptian- Iraqi – and for the favorite of the Egyptian sample, and there was no statistical significance differences in the( Libyan – Iraqi group). In light of the results, the researcher presents some recommendations and suggestions.